CIRC Type Cooperative Learning Model in Learning Arabic Rules - Syaifudin, Mochamad; Muhammad Sofwan bin Harizan (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
Arabic rules are one of the elements of language other than sounds  (al-Aswat) and vocabulary (al-Mufrodat) and are important in learning sentence structure in Arabic. Without it, Arabic would not be understood, because it could not determine subjects, predicates, objects, and descriptions. However, most students have difficulty in understanding it, in addition to many new terms that are unfamiliar when compared to terms in Indonesian or English also changes at the end of words (i'rob) whether the change is in the form of letters or letters. Based on that problem, the right learning model is needed in its delivery. This article will discuss one of the models for learning Arabic rules, namely the CIRC (Cooperative Integrated Reading And Composition) learning model. This article uses the Library Research method, with data sources in the form of books, and journals, both online and offline, to obtain information relevant to the problem discussed, especially to describe theoretical studies that have been determined. The findings of this article explain that the CIRC learning model is more appropriate in improving reading and writing skills because the rules of Arabic are only limited to being a medium, not a goal, learning it is more appropriate by using direct methods by providing exercises related to the number of sentences in Arabic. The implication of this article states that CIRC is one of the learning models that can be developed to achieve competency in understanding the Arabic rules of students.